2018
DOI: 10.1097/scs.0000000000004746
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Reconstruction for Pediatric Patients

Abstract: In conclusion, treating pediatric patients with tumor pathology requires an experience pediatric team to get good outcomes. Surgeons must consider that pediatric patients are in constant growth and development but that must not be an issue in resection and reconstruction decisions. Literature review shows that, as in adults, free flaps seem to be the criterion standard for big resections in mandibles defects, and are safe to use in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
2
8
1
Order By: Relevance
“…Our study was limited by the low prevalence of pediatric mandibular lesions necessitating resection and reconstruction. Only 24 patients were located through our search, and the low number contained in our study population was consistent with previous studies on the subject 1,3,9–11,18,21,22,26 . Although our study detected statistical differences in the number of trips to the operating room for complications and early major complications between the high and low RI groups, it was underpowered to detect statistical significance when assessing for late major complications and minor complications.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our study was limited by the low prevalence of pediatric mandibular lesions necessitating resection and reconstruction. Only 24 patients were located through our search, and the low number contained in our study population was consistent with previous studies on the subject 1,3,9–11,18,21,22,26 . Although our study detected statistical differences in the number of trips to the operating room for complications and early major complications between the high and low RI groups, it was underpowered to detect statistical significance when assessing for late major complications and minor complications.…”
Section: Discussionsupporting
confidence: 75%
“…Only 24 patients were located through our search, and the low number contained in our study population was consistent with previous studies on the subject. 1,3,[9][10][11]18,21,22,26 Although our study detected statistical differences in the number of trips to the operating room for complications and early major complications between the high and low RI groups, it was underpowered to detect statistical significance when assessing for late major complications and minor complications. Although the difference between the percentage of patients experiencing these adverse outcomes were high, 67% versus 42% for late major complications and 50% versus 25% for minor complications, post hoc power analysis demonstrated a sample size of 61 patients in each group would be required to detect significant change in these outcomes.…”
Section: Discussioncontrasting
confidence: 57%
“…8 This suggests that free flap reconstruction may be performed successfully in pediatric patients, with minimal risk of free flap failure. 2,8,13 Unlike the study by Liu which reports outcomes for fasciocutaneous and osteocutaeous flaps in the pediatric population, our study reports flap outcomes for fibula flaps with specific outcomes for fibula donor site complications. 8 Additionally, our study uniquely reports outcomes on long-term craniofacial growth.…”
Section: Discussionmentioning
confidence: 93%
“…Prior studies suggest that reconstructed hemimandibulectomy defects undergo growth over time with minimal asymmetry and are facilitated by the preservation of the mandible epiphyseal growth plates and condyle. 2,4,9,21,23,24 Furthermore, a study by Temiz in 2015 demonstrated pediatric patients experienced normal facial symmetry and growth following mandibular defect reconstruction with fibula flaps, suggesting fibula flaps grow with patients' mandibles over time. 5,25 The results of this study are limited by the number of patients available for inclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation